Case report: Hemophagocytic lymphhistiocytosis - hojaili, Dr Najia al; alzahrani, Dr Attia; al harthy, Dr Wafaa; Kotbi, Dr Ibraheem; masmali, Dr Hossan; Bahr Aldin, Dr Soad (Journal of Medical Biomedical and Applied Sciences, 2018)
see the pdf